Efektivitas Media Pembelajaran Simulasi PhET Terhadap Kemampuan Literasi Digital Dan Hasil Belajar Siswa Pada Materi Elastisitas Dan Hukum Hooke - Koilmo, Olifa; Suban Hali, Antonius; Kameo, Welhemina (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2025)
Digital literacy is one of the most important skills for students to master in the current digitalization era. The use of technology-based learning media has a considerable impact on students' digital literacy skills. This can help students in developing digital literacy skills through the use of interactive learning media. The purpose of this study was to determine the effectiveness of PhET simulation virtual lab learning media on digital literacy skills and student learning outcomes. This research is a type of pre-experiment research with a one group pretest-posttest research design. The subjects of this study were all students of class XI IPA 2 SMA Negeri Kapan, totaling 30 students. The results of the data were analyzed using the N-Gain test and obtained data on students' digital literacy skills with an average N-Gain value of 0.73>0.7 and N-Gain percentage (%) of 73>70, and student learning outcomes obtained from the average N-Gain value of 0.72>0.7 and N-Gain percentage (%) of 72>70. Based on data analysis, it is said that the use of PhET simulation virtual lab learning media is effective in improving digital literacy skills and student learning outcomes